Is the COVID-19 Matters for Islamic Banking Performance? A Cross-Countries Analysis - Rindang Nuri Isnaini Nugrohowati; Faaza Fakhrunnas (ETIKONOMI, 2024)
Research Originality: Considering the originality of the study to have a deeper investigation on the impact of the pandemic on bank’s risk and return.Research Objectives: This study aims to identify the impact of Covid-19 on bank performance and risk levels.Research Methods: This study focuses on Islamic banks in 12 countries with the most developed financial sector during the 4th quarter of 2016 to the 1st quarter of 2022. The data analysis method in this study adopts panel data analysis with a fixed effect model.Empirical Results: The finding of the study shows that the Covid-19 pandemic resulted in a decline in the performance of Islamic banks, as seen from the ratio of return on average asset, return on equity, net profit margin, return on average asset, and return on average equity. However, an interesting finding from this research is that there is no concern about worsening bank risk levels as reflected in the nonperforming financing, Z-Score, and leverage ratio. Meanwhile, the control variables, bank size and inflation rate, also affect the performance and risk of Islamic banks.Implications: The study implies that banking practitioners and financial authority for the banking sector are required to issue some financial strategies in order to achieve and maintain a certain level of financial performance, especially during financial turmoil. JEL Classification: G20, G21, G28 How to Cite:Nugrohowati, R. N. I., & Fakhrunnas, F. (2024). The COVID-19 Matters for Islamic Banking Performance? A Cross-Countries Analysis. Etikonomi, 23(1), 201 – 218. https://doi.org/10.15408/etk.v23i1.31243.